2023
DOI: 10.1136/jitc-2022-006345
|View full text |Cite
|
Sign up to set email alerts
|

ANXA1-derived peptide for targeting PD-L1 degradation inhibits tumor immune evasion in multiple cancers

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) therapy targeting programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) shows promising clinical benefits. However, the relatively low response rate highlights the need to develop an alternative strategy to target PD-1/PD-L1 immune checkpoint. Our study focuses on the role and mechanism of annexin A1 (ANXA1)-derived peptide A11 degrading PD-L1 and the effect of A11 on tumor immune evasion in multiple cancers.MethodsBinding of A11 to PD-L1 was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD-L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways. [46][47][48][49][50][51][52] For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X. By stabilising DDX3X, USP7 increases Wnt/beta-catenin signalling, which has previously been demonstrated to be strongly correlated with colorectal cancer cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD-L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways. [46][47][48][49][50][51][52] For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X. By stabilising DDX3X, USP7 increases Wnt/beta-catenin signalling, which has previously been demonstrated to be strongly correlated with colorectal cancer cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Deubiquitylases have been implicated with a number of cancers, including HCC, according to recent research. USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD‐L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways 46–52 . For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Induction of PD-L1 degradation in proteasome is triggered by E3 ubiquitin ligases such as Cullin3, SPOP [25] STUB1, [26] 𝛽-TrCP, [27] RNF125, [28] ITCH, [29] ariadne RBR E3 ubiquitin protein ligase 1 (ARIH1), [30] membrane-associated RING-CH 8 (MARCH8), [31] and HRD1. [32] Furthermore, PD-L1 degradation in proteasome could be caused by albendazole/ubiquilin 4 pathway, [33] annexin A1 -derived peptide A11/USP7 pathway, [34] and ISG15 ubiquitin-like protein. [35] In addition to proteasomal-dependent degradation, PD-L1 could be degradation in lysosome by different pathways such as PKC𝛼/GSK3𝛽/MITF, [36,37] SA-49/PKC𝛼/GSK3𝛽/MITF, [38] IPAG/Sigma-1, [39] MTSS1/AIP4, [40] TBM-1/mTORC1/TFEB, [41] and amlodipine/calcium flux.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, USP8 inhibits the ubiquitination-regulated proteasome degradation pathway by positively interacting with PD-L1 and upregulating its expression [ 81 ]. USP7 mediates the ubiquitination of PD-L1 and inhibits its degradation [ 82 ]. Additionally, UCHL1 promotes PD-L1 deubiquitination and upregulates its expression in NSCLC [ 83 ].…”
Section: Preclinical Study Of Ptms Promoting Pd-l1 Expression and Fun...mentioning
confidence: 99%
“…Similarly, a study on a USP8 inhibitor demonstrated its effectiveness in suppressing pancreatic tumor growth by activating killer T cells, especially when combined with anti-PD-L1 therapy [ 81 ]. Additionally, A11, an inhibitor of USP7, showed promising antitumor effects by blocking PD-L1’s ability to help tumors evade immune detection, and when combined with PD-1 antibody therapy, it showed enhanced antitumor activity [ 82 ]. Additionally, the application of the CSN5 inhibitor curcumin inhibited the ubiquitination of PD-L1, reduced PD-L1 expression, and increased the sensitivity of tumor cells to CTLA4 immunotherapy [ 73 ].…”
Section: Therapeutic Prospects and Clinical Transformation Of Pd-1/pd...mentioning
confidence: 99%